2018
DOI: 10.3390/su10072492
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Vertical Linkage of Greenhouse Gas Emission Intensity Change of the Animal Husbandry Sector between China and Its Provinces

Abstract: China's carbon intensity (CI) reduction target in 2030 needs to be allocated to each province in order to be achieved. Thus, it is of great significance to study the vertical linkage of CI change between China and its provinces. The existing research on the vertical linkage focuses more on energy-related economic sectors in China; however, attention has not been paid to China's animal husbandry (AH) sector, although the role of the China's AH sector in greenhouse gas (GHG) reduction is increasingly important. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In their paper, Cai et al [9] carry out a national level study on a reduction of the emission intensities (per unit of the monetary value of output) of non-CO 2 greenhouse gases arising from the livestock sector in China, through an analysis of the contribution of each province to the overall national emissions. They especially concentrate on the role of three "driving factors," i.e., environmental efficiency, productive efficiency and economic share, in determining the national greenhouse gas emission intensity.…”
mentioning
confidence: 99%
“…In their paper, Cai et al [9] carry out a national level study on a reduction of the emission intensities (per unit of the monetary value of output) of non-CO 2 greenhouse gases arising from the livestock sector in China, through an analysis of the contribution of each province to the overall national emissions. They especially concentrate on the role of three "driving factors," i.e., environmental efficiency, productive efficiency and economic share, in determining the national greenhouse gas emission intensity.…”
mentioning
confidence: 99%
“…In his proposal, Cai suggested that in order to achieve China's carbon intensity reduction target for 2030, it should be allocated to each province. He also explored the vertical linkage relationship between China and its 31 provinces' livestock carbon emission intensity changes using the Logarithmic Mean Divisia Index model (LMDI) [15]. While there are studies suggesting the importance of integrating the unique aspects of animal husbandry development in various provinces and examining the factors and methods of carbon emissions from animal husbandry based on local conditions, there is currently a lack of literature on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock production accounts for a significant share of the global greenhouse gas (GHG) balance, including carbon dioxide (CO 2 ), methane (CH 4 ), ammonia (NH 3 ), and nitrous oxide (N 2 O) released into the atmosphere (7). There are many calculation and assessment methods to study carbon emission efficiencies, such as the stochastic frontier model, regression model, data envelopment analysis (DEA) method, and unexpected output (Slack-Based Measure) model (8)(9)(10)(11). Most studies have adopted the unexpected output (Slack-Based Measure) model to calculate carbon emission efficiency.…”
mentioning
confidence: 99%